Potent single-domain antibodies that arrest respiratory syncytial virus fusion protein in its prefusion state - Iebe Rossey (Nature Portfolio, 2017)
Neutralizing antibodies for respiratory syncytial virus (RSV) can reduce disease in hospitalized children, but current options show limited efficacy. Here, the authors isolate potent single-domain antibodies from llamas that recognize the prefusion conformation of RSV F and prevent RSV replication in mice.